ANALYSIS OF THE COMPETITIVENESS OF THE VEGETABLE SECTOR OF THE REPUBLIC OF MOLDOVA - Anatolie IGNAT; Sergiu TIRIGAN; Eugenia LUCASENCO (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
This paper presents a general overview and analysis of the Moldovan vegetable sector. The purpose of the article is to obtain a comprehensive picture of the Moldovan vegetable sector's value chain. The results of the paper are based on the primary and secondary information collected from different data sources. The primary tool for collecting the information was the individualized interview with different categories of participants on the Moldovan vegetable market, as well as the questionnaires made on a sample of 65 consumers. Thus, 65 consumers were questioned both in supermarket chains and in agricultural markets to identify their consumer preferences. Discussions were also held and 10 persons responsible for procurement from commercial units have been interviewed in order to analyze the model for integrating distribution units into the value chain in the vegetable sector. Conclusions on the competitiveness of the sector allow us to note that most of the analyzed vegetables sold on the market are produced by agricultural enterprises and peasant farms with areas over 10 ha and the access of domestic vegetable producers to the supermarket market is affected by a series of problems.